Feelings about School in Gifted and Non-Gifted Children: What Are the Effects of a Fine Art Program in Primary School? - Christine Sanchez; Nathalie Blanc (MDPI AG, 2023)
There is a consensus about the benefits of an artistic activity on health and well-being. In France, a gifted child is considered a special needs student for whom enrichment is advocated. Therefore, this study examines the extent to which a whole-class art enrichment program delivered to both gifted and non-gifted children benefits both student populations with respect to their school well-being. The art program was implemented in classrooms over the course of an entire school year (during the COVID-19 pandemic). The self-report French version of the Feelings About School scale (i.e., FAS) was completed in three steps (i.e., before, mid-program, and after) by a sample of gifted and non-gifted children benefiting from the program. The FAS scores of those students were also compared at the end of the school year with those of students who did not participate in the art program. Despite the pandemic context that requires caution in drawing definite conclusions, this study supports that (i) the fine arts practice is a lever of development, (ii) the sanitary situation was detrimental for elementary school students, and (iii) better adaptive capacities were exhibited by gifted children in this context.